Penerapan Kerangka TPACK untuk Meningkatkan Hasil Belajar Matematika Unsur-unsur Bangun Datar Siswa Kelas 3 SD - Lailatul Fitriyah; Budi Lestari; I Ketut Suastika (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study was motivated by the low student learning outcomes, as shown by the pretest results with a class average score of 58.2 and a learning completeness percentage of only 29%. The study aimed to improve students’ mathematics learning outcomes on the topic of plane figure elements through the implementation of the Technological Pedagogical Content Knowledge (TPACK) framework in third-grade students at SDN Karangbesuki 3 Malang. This research used the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, which consisted of two cycles, with each cycle including planning, action, observation, and reflection stages. The research subjects were 28 students. Data were collected through learning outcome tests and observations. The learning process was carried out using interactive PowerPoint, the Polypad application, Wayground, cooperative learning models, and concrete media. The results showed that the implementation of the TPACK framework was able to improve students’ learning outcomes. In Cycle I, the class average increased to 72.1 with a learning completeness percentage of 57%. In Cycle II, the class average increased again to 83.2 with a learning completeness percentage reaching 82%. These results indicate that the research success indicators had been achieved. Therefore, the implementation of the TPACK framework proved effective in improving mathematics learning outcomes on the topic of plane figure elements for third-grade students at SDN Karangbesuki 3 Malang.